Analisis indikator makro ekonomi terhadap Jakarta Islamic Index - Dini, Dini Rahmayanti (Journal of Economics Research and Policy Studies, 2021)
Stock price fluctuations in various sectors continue to show a decline because of the Covid-19 pandemic. This is because of its nature, which is strongly influenced by external changes or fundamental information. Here, the ability of investors to understand will influence investors' decisions to invest. This study aims to determine the effect of macroeconomic indicators on the Jakarta Islamic Index, the observation period 2015-2021, using monthly time series data. Macro indicators used in analyzing the stock of the Jakarta Islamic Index are inflation, interest rates, industrial production growth, crude oil, exchange rates, and the industry average Dow Jones as global index variables. The analysis technique used is multiple linear regression. Simultaneous test results show that the macro variable indicators and DJIA have a significant effect on JII. The results of the partial test show that inflation and DJIA have a significant positive effect on JII, while the exchange rate and crude oil have a significant positive effect on JII, for the variables of industrial production growth and interest rates have no significant effect on JII.